MANAJEMEN KURIKULUM MERDEKA DALAM PENINGKATAN PEMBELAJARAN EFEKTIF DI SMP NEGERI 1 MOJOWARNO JOMBANG - Mohammad Afif Jauharil Bawazir; Nur ‘Azah Nur ‘Azah (JOURNAL SAINS STUDENT RESEARCH, 2024)
Independent Curriculum Management is one of the most important things in improving effective learning. This does not negate the role of independent curriculum management in its implementation. Therefore, in order for desired educational outcomes to be achieved optimally and in accordance with expectations, it is necessary to have independent curriculum management to improve effective learning. Effective learning is learning that allows students to learn easily, have fun and achieve learning goals in accordance with expectations. This research uses a case study type of research. The research was carried out using a qualitative approach with descriptive methods. Data collection was carried out using in-depth interview techniques, observation and documentation. The informants in this research consisted of the school principal, head of curriculum and teachers. The data analysis techniques used are: data reduction, data display, and verification. Checking the validity of the data is based on four criteria of credibility, transferability, dependability and confirmability. 1). Curriculum planning, organizing the curriculum, implementing the curriculum, supervising the curriculum and assessing all activities. 2). Increasing effective learning with various learning models. 3). Independent curriculum management focuses on improving effective learning with learning innovations that aim to develop students' learning potential and interest. 4) factors for independent curriculum management in improving effective learning at SMP Negeri 1 Mojowarno, Jombang.